The G.I. Bill and Underemployment - Ciprian Domnisoru (Institute of Labor Economics (IZA), 2023)
While the ill luck of graduating during a recession is understood to potentially result in job mismatch, less is known about the drivers of underemployment outside of business cycles. This paper shows that the college subsidy investments undertaken as part of the WWII, Vietnam War, and Post-9/11 G.I. Bills led to persistent and sizable increases in the underemployment rate among bachelor's degree holders. In turn, underemployment explains approximately a quarter of the earnings penalty experienced by recent college educated veterans, over and above lost labor market experience, lower rates of graduate school completion and combat exposure effects.
Keywords: I22; J24; J31; 330; underemployment; veterans; subsidies